A paradigm shift in bioavailability enhancement using solid self emulisifying drug delivery system - Umadevi, Sankararajan; Senthil Boopathi, Rajathi; Ezhilarasan (Journal of Applied Pharmaceutical Research, 2025)
Background: Solids are physically and chemically more stable compared to liquid formulations. The Solid SEDDS form is preferred over the liquid SEDDS form to enhance the oral bioavailability of lipophilic medications. Solid SEDDS are isotropic mixtures of oil, surfactant, and co-solvent. Methodology: A liquid-solid compact approach is followed to convert liquid SEDDS into solid SEDDS. Melt granulation, melt extrusion, spray drying, adsorption to solid carriers, and freeze drying are some approaches to converting liquid SEDDS into solid SEDDS. Various solid self-emulsifying materials in several solid dosage forms, like solid dispersions, tablets, capsules, and powders. Result and discussion: Solid SEDDS results in solubility studies, particle size and polydispersity index (PDI), zeta potential, in vitro drug release, solid-state characterization (e.g., XRD, DSC), and stability studies. In summary, S-SEDDS seems to be a viable strategy for improving the distribution of poorly water-soluble drugs through enhanced bioavailability, stability, and administration simplicity. Conclusion: In this review, the research will be extended to the different approaches toward improving the bioavailability, stability, and solubility of poorly soluble drugs into solid SEDDS. All these components are intended to act as primary instructions for future development in SSEDDS.